Constructs for understanding Japan - Sugimoto, Yoshio; Mouer, Ross E. 1944- (K. Paul International, 1989)
"A multi-cultural and multi-discplinary volume that explores a variety of revisionist perspectives of interpreting Japanese society by examining individuals, institutions and methodology as the three foci of analysis"-- Cover flap